PERAN MANAJEMEN KEPEMIMPINAN DALAM MENGOPTIMALKAN PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL UNTUK PEMBELAJARAN EFEKTIF - Yul, Fadlul Amdhi; Giatman, M; Maksum, Hasan; Lapisa, Remon (STKIP Pesisir Selatan, 2025)
The role of leadership management in optimizing the use of digital learning media to achieve more effective learning at the junior high school level. The importance of this research lies in the crucial role of effective leadership in managing educational technology, especially amidst the rapid development of digitalization in the education sector. This study adopted a quantitative design with a correlational survey approach, involving 28 seventh-grade students at SMPN 10 Bengkulu City. The sampling technique used was purposive sampling, selecting students who actively use digital learning media. The collected data were analyzed using linear regression analysis and Pearson correlation to test the relationship between variables. The results of the study indicate a significant relationship between leadership management and the use of digital learning media, as well as a positive influence of digital media use on learning effectiveness. These findings provide a practical contribution to education policy, by encouraging the strengthening of leadership roles that support the use of technology in learning. Theoretically, this study enriches the understanding of the transformational leadership model in the context of digital education and provides a basis for developing technology-based learning management strategies.